2007
DOI: 10.1110/ps.062667407
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proteins with dimethylarginines in Escherichia coli for protein–protein interaction studies

Abstract: Protein arginine methylation often modulates protein-protein interactions. To isolate a sufficient quantity of proteins enriched in methyl arginine(s) from natural sources for biochemical studies is laborious and difficult. We describe here an expression system that produces recombinant proteins that are enriched in v-N G ,N G -asymmetry dimethylarginines. A yeast type I arginine methyltransferase gene (HMT1) is put on a plasmid under the control of the Escherichia coli methionine aminopeptidase promoter for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…The recombinant expression of arginine methylated proteins in E. coli has previously been reported for two yeast proteins, Sbp1p and Stm1p, which were co-expressed with yeast type I arginine methyltransferase (Hmt1p) (Hsieh et al, 2007). In our hands, a simple co-expression from a bicistronic plasmid did not result in quantitative hnRNP K methylation.…”
Section: Production Of Methylated Hnrnp Kmentioning
confidence: 50%
“…The recombinant expression of arginine methylated proteins in E. coli has previously been reported for two yeast proteins, Sbp1p and Stm1p, which were co-expressed with yeast type I arginine methyltransferase (Hmt1p) (Hsieh et al, 2007). In our hands, a simple co-expression from a bicistronic plasmid did not result in quantitative hnRNP K methylation.…”
Section: Production Of Methylated Hnrnp Kmentioning
confidence: 50%
“…Dense methylation of GAR domains is emerging as a common theme amongst protein arginine methyltransferase (PRMT) substrates [16,48], and the lack of strong enrichment techniques for methylated peptides suggests that recombinant PRMT substrate production is likely to play an important role in the comprehensive localization of these sites [6,49]. As additional PRMT substrates are identified and targeted for methylarginine site localization, the benefits of the abovementioned PTM-specific targeted data acquisition workflow should be particularly marked.…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of the RGG domain of Sbp1 were known to modulate its molecular interactions in the cell (Hsieh et al 2007). In this study, we demonstrated that arginine methylation in the RGG repeats of Sbp1 compromised the binding of Sbp1 to Pab1.…”
Section: Arginine Methylation Of Sbp1 Compromises Its Interactions Wimentioning
confidence: 66%
“…S2A; Hsieh et al 2007). We then confirmed methylation of arginines in the RGG domain by mass spectrometry (Supplemental Fig.…”
Section: Formation Of a Stablementioning
confidence: 98%
See 1 more Smart Citation